Genre, cycles and sunshine noir television. Issue 2 (1st October 2017) - Jenner, Mareike
This article explores the concept of television cycles, using the American sunshine noir cycle as an example. To conceptualize television cycles, this article draws heavily on Amanda Ann Klein's work on American film cycles and puts the television cycle in relation to notions of genre, sub-genre and individual texts. In a second step, this article will analyse a specific example, the sunshine noir, a cycle present in American television in the 1980s and 1990s and most commonly associated with Miami Vice (1984–89). The sunshine noir is part of the crime genre and describes detective narratives that draw on film noir of the 1930s and 1940s and neo-noir films from the 1980s and 1990s and reconfigure elements of style and narrative to fit the narrative and industrial needs of television.